Pengaruh Inovasi Produk, Persepsi Harga dan Kualitas Layanan terhadap Kepuasan Pelanggan Kopi Caffe on Wheels di Jakarta - Sheyla Ayu Oktaviani; Rojuaniah Rojuaniah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The main objective of this research is to examine the influence of product innovation, price perceptions, and service quality on customer satisfaction with coffee on wheels in Jakarta. The sampling technique used in this research was non-probability sampling, specifically the purposive sampling method, with a total of 125 respondents who met the criteria of being over 17 years of age and having purchased coffee products from coffee on wheels more than twice in the last month. The analysis method employed is multiple linear regression analysis. The findings show that product innovation does not have a significant effect on customer satisfaction. However, price perception has a positive effect on customer satisfaction, indicating that customers are more satisfied when they perceive the price to be appropriate. Additionally, service quality has a positive impact on customer satisfaction, meaning that good service enhances overall satisfaction. Moreover, the combination of price perceptions and service quality together significantly influences customer satisfaction. These results suggest that maintaining appropriate pricing and high service quality can lead to higher customer satisfaction with coffee on wheels.